Evolving the Assessment of Clinical Judgment: An Individual or Collective Competency?. Issue 2 (19th March 2023) - Delle, Janelle M.; Cross, Lacey; Weaver, Angela; Jessee, Mary Ann
Abstract : Background: Nurses make decisions about care individually and as part of a team. Collective competence, the effective team management of patient care situations, is partially dependent on nurses' individual confidence and clinical judgment competence. Purpose: To describe individual and team-based facilitators and barriers to collective competence in teams of senior baccalaureate-level prelicensure nursing students during a team-based simulation. Methods: With a cross-sectional design, the study used a 26-item survey based on the National Council of State Boards of Nursing (NCSBN)-Clinical Judgment Measurement Model (CJMM) (α= .86) to assess individual student confidence and perceptions of clinical judgment competence while observation of team dynamics and task completion assessed collective competence. Results: Closed-loop communication and role assignment were facilitators of collective competence when present and barriers when absent. Additional barriers were lack of student confidence and perceived competence with Layers 3 and 4 of the NCSBN-CJMM. Conclusions: Team-based simulation strategies can be effectively used to assess collective clinical judgment competence.